Metaphorical Framing of Natural Disasters in Media Discourse - Nurgazina, Assel Tanatkanovna; Mongilyova, Natalya Viktorovna; Ismagulova, Gulnar Kulmukhambetovna (Forum for Linguistic Studies, 2025)
Amidst escalating climate threats and the increasing frequency of natural disasters, media discourse has become a central arena for shaping public risk perception, mobilization strategies, and collective responses. Metaphor serves as a key cognitive and discursive instrument for meaning construction, framing interpretation, and embedding culturally resonant models of perception. The analysis of metaphorical framing provides insight into the mechanisms of crisis communication, environmental rhetoric, and collective sense-making. This study examines and systematizes metaphorical frames in English-language media discourse on natural disasters. The corpus comprises BBC and Voice of America texts (2023–2024) covering wildfires and floods, thus enabling a symmetrical comparison of British and American media ecosystems. The theoretical foundation integrates conceptual metaphor theory, frame semantics, critical discourse analysis, and Critical Metaphor Analysis (CMA). The methodology combines corpus-based procedures (frequency, collocational, and contextual analysis in AntConc) with the MIPVU protocol for metaphor identification, ensuring reliability through corpus symmetry and inter-annotator verification. The study introduces the concept of a “frame index” – a quantitative metric for assessing metaphorical intensity thereby expanding the methodological repertoire of cognitive-discursive analysis. The research aims to identify the dominant types of metaphorical framing of natural disasters, describe their cognitive-discursive functions, and trace their variation across media platforms and disaster types. The findings contribute to the advancement of cognitive linguistics and media discourse analysis and hold practical value for enhancing environmental communication, media education, and editorial standards in reporting climate risks.